2014
DOI: 10.4037/ajcc2014997
|View full text |Cite
|
Sign up to set email alerts
|

Science-Driven Care: Can Education Alone Get Us There by 2020?

Abstract: M ore than a decade ago, the Institute of Medicine (IOM) recognized evidence-based practice (EBP) as a key solution to ensure that the care delivered has the highest clinical effectiveness known to science.1 To reach the IOM's 2020 goal that "90% of clinical decisions will be supported by accurate, timely and up-to-date clinical information, and will reflect the best available evidence," 2(p4) clinicians need EBP competencies to guarantee that applicable research findings are integrated into clinical situat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Poor staff adherence to infection prevention practices and policies during insertion, poor care for the devices after insertion, and extended durations of catheter use are all important factors for the development of serious and costly infections. 26,30 Patients deserve to have a healthy hospital environment with the least possible risks during the course of their hospital stay. Halm 30 points to an environment where the "search for and use of evidence" is contributory to an evidence-based culture, effecting improved outcomes in nursing.…”
Section: Discussionmentioning
confidence: 99%
“…Poor staff adherence to infection prevention practices and policies during insertion, poor care for the devices after insertion, and extended durations of catheter use are all important factors for the development of serious and costly infections. 26,30 Patients deserve to have a healthy hospital environment with the least possible risks during the course of their hospital stay. Halm 30 points to an environment where the "search for and use of evidence" is contributory to an evidence-based culture, effecting improved outcomes in nursing.…”
Section: Discussionmentioning
confidence: 99%
“…A recent evidence synthesis reported 10 studies evaluating the effectiveness of educational interventions in building EBP attitudes, knowledge, skills, and behaviors of nurses (Halm, ). Interventions were primarily workshop or immersion programs, but seminars, journal clubs, and EBP and research councils were also evaluated via: (a) self‐reported EBP attitude, knowledge, and behavior (Chang et al., ; Dizon, Somers, & Kumar, ; Edward & Mills, ; Leung, Trevana, & Waters, ); (b) PICO questions and activity diaries (Dizon et al., ); (c) Edmonton Research Orientation (Gardner, Smyth, Renison, Cann, & Vicary, ) and Clinical Effectiveness or EBP Questionnaire (Sciarra, ; Toole, Stichler, Ecoff, & Kath, ; White‐Williams et al., ); and (d) interviews and focus groups to identify qualitative themes about nurses’ experience in EBP programs (Balakas, Sparks, Steurer, & Bryant, ; Nesbitt, ; Wendler, Samuelson, Taft, & Eldridge, ).…”
Section: Introductionmentioning
confidence: 99%